2009
DOI: 10.1021/jp810281f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ovalbumin in the Stabilization of Metastable Vaterite in Calcium Carbonate Biomineralization

Abstract: The role of proteins in biomineralization has been examined in this work by studying the effect of ovalbumin on the stabilization of metastable CaCO(3) phases. In the absence of ovalbumin, the mixing of Na(2)CO(3) with CaCl(2) in an aqueous solution led to the formation of metastable phases that swiftly transformed into stable calcite crystals within 4 h under the experimental conditions. However, ovalbumin was found to favor the formation and stabilization of spherical vaterites, and the effect was concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 33 publications
7
79
0
Order By: Relevance
“…The calcium cations are the starting points for the subsequent formation of ACC nuclei which then undergo a series of phase transitions to the stable crystalline polymorphs [64]. The ability of OVAL to stabilise unstable calcium carbonate phases was further confirmed using in vitro experiments [65,66]. In our study, we observed that ovalbumin, which is overabundant at 7h p.o., is a major protein with high emPAI values at all stages (5 th , 6 th , 2 nd and 7 th most abundant protein at 5, 6 and 7 and 16 hours p.o.…”
Section: Ovalbumin (Oval) Had Been Identified Previously In the Eggshsupporting
confidence: 61%
See 1 more Smart Citation
“…The calcium cations are the starting points for the subsequent formation of ACC nuclei which then undergo a series of phase transitions to the stable crystalline polymorphs [64]. The ability of OVAL to stabilise unstable calcium carbonate phases was further confirmed using in vitro experiments [65,66]. In our study, we observed that ovalbumin, which is overabundant at 7h p.o., is a major protein with high emPAI values at all stages (5 th , 6 th , 2 nd and 7 th most abundant protein at 5, 6 and 7 and 16 hours p.o.…”
Section: Ovalbumin (Oval) Had Been Identified Previously In the Eggshsupporting
confidence: 61%
“…calcium carbonate formation and ACC stabilisation has been investigated [63][64][65][66]. Calcium is bound by ovalbumin and this accumulation creates a nucleation centre for the minerals [64].…”
Section: Ovalbumin (Oval) Had Been Identified Previously In the Eggshmentioning
confidence: 99%
“…The mechanism of vaterite stabilisation, therefore, appears to be due to the greater adsorption of the tetrazole after formation of the vaterite and this adsorption impedes its dissolution, thereby hindering any transformation to calcite. While this is sometimes used to explain the impact of large protein molecules on vaterite stabilisation [23,24], templating effects tend to be cited more often [25][26][27][28][29][30]. Our hypothesis, however, is supported by both the visual appearance of the vaterite after 14 days in the presence of the tetrazole and by the adsorption of the tetrazole onto the vaterite surface from DRIFT analysis.…”
Section: Discussionmentioning
confidence: 71%
“…However, since vaterite is rather unstable in a humid environment, this porous CaCO3 will easily convert to non-porous rhombohedral calcite overnight [16]. Recently, several modification approaches, such as layer-by-layer electrostatic adsorption, double hydrophilic block copolymers coating, and nanodots embedding, have been attempted to stabilize vaterite MPs [14,[17][18][19]. The above foreign impurities can inhibit the nucleation of calcite from metastable vaterite phase.…”
Section: Introductionmentioning
confidence: 99%